Protective effect of astragaloside IV on cadmium-induced spermatogenesis microenvironment damage in rats. (4th May 2022) - Ning, Wei; Liao, Xiaogang; Dong, Xingyou; Wang, Yangcai; Yang, Xingliang; Xu, Jie; Yi, Shanhong; Yang, Zhenxing
ABSTRACT: The previous study using Sertoli cells cultured in vitro has shown that the protective effects of astragaloside IV (AsIV) on cadmium (Cd)-induced damage to Sertoli cells and its membrane proteins. Yet, it is not known if AsIV has an equivalent effect on Cd-induced damage to the spermatogenesis microenvironment in rats. Using an in vivo model, Cd-induced damage to the spermatogenesis microenvironment and the protective effects of AsIV were studied. Eighteen male Sprague Dawley (SD) rats were randomly divided into three groups (n = 6/group): Cd group, Cd&AsIV group, and control group. Cd was administered to the rats in the Cd group via i.p. at 1 mg/kg body weight once daily, Cd and AsIV was administered to the rats in the Cd&AsIV group via i.p. at 1 mg/kg body weight and 10 mg/kg body weight respectively once daily, and the same volume of saline was administered to the rats in control group via i.p. once daily. The rats in the three groups were injected continuously for 5 days. Vesicular formation in the seminiferous tubules was observed in the Cd treatment group. The average optical density of claudin-11, zonal occludin-1 (ZO-1), and connexin 43 (Cx43) decreased significantly in the Cd treatment group. The ultrastructural damage of the Sertoli cells and tight junctions were also observed by electron microscopy. AsIV treatment rescued the morphologic changes of the seminiferous tubules of the testis and the ultrastructural damage of the Sertoli cells and tight junctions. The average optical density of claudin-11, ZO-1, and Cx43 also increased significantly after AsIV treatment. Cd damages the spermatogenesis microenvironment in rats, which can be rescued by AsIV treatment. These results illustrate that AsIV may also have a protective effect on Cd-induced damage to the spermatogenesis microenvironment in rats. Abbreviations: AsIV: astragaloside IV; Cd: cadmium; SD: Sprague Dawley; ZO-1: zonal occludin-1; Cx43: connexin 43; BTB: blood-testis barrier; MAPKs: mitogen-activated protein kinases; OSP: oligodendrocyte-specific protein; Cxs: connexins; GJIC: gap junctional intercellular communication; ROS: reactive oxygen species; MDA: malondialdehyde; TGF: tumor growth factor; PBS: phosphate buffer saline; BSA: bovine serum albumin